RELATIONSHIP OF ELDERLY KNOWLEDGE LEVEL WITH PARTICIPATION IN IMPLEMENTATIONGYMNASTIC IN THE CITY OF SEMARANG - dewi elliana (Universitas Muhammadiyah Semarang, 2019)
Old age is said to be the final stage of development in human life. Efforts to support the achievement of life expectancy begin with improving services in the field of health in the elderly. In Indonesia in 2010 there were 23,992,513 elderly people. The purpose of this study was to determine the relationship of the level of knowledge of the elderly about elderly gymnastics with participation in the implementation of elderly gymnastics in Pudakpayung Village, Banyu Manik District, Semarang City. This study used a cross sectional design and included the type of correlation. In this study the sampling technique used purposive sampling with as many as 80 respondents. The data is then analyzed using Chi Square Test. This research was conducted in May 2014. The results of the study showed that the level of knowledge of the elderly about elderly gymnastics was mostly included in the category of 37 (46.3%) respondents. While the participation in the exercise of elderly gymnastics, mostly including the category did not follow as many as 39 (48.8%) respondents. The conclusion of this study is that there is a relationship. The value of the level of knowledge of the elderly about elderly gymnastics with participation in the implementation of elderly gymnastics with a p value of 0,000. The value of p value is smaller than 0.05 (0,000 <0,05). Suggestions given to the community, especially the elderly, increase their knowledge about the benefits of elderly gymnastics by actively digging up information and knowledge about the benefits of elderly gymnastics for health both through elderly posyandu or other more accurate sources